2010
DOI: 10.1152/ajpgi.00076.2010
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor reduces autophagy in intestinal epithelium and in the rat model of necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a devastating intestinal disease of premature infants. Epidermal growth factor (EGF) is one of the most promising candidates in NEC prophylaxis. Autophagy regulates cell homeostasis, but uncontrolled activation of autophagy may lead to cellular injury. The aim was to evaluate the effects of EGF on intestinal autophagy in epithelial cells and in the rat NEC model and measure autophagy in NEC patients. Intestinal epithelial cells (IEC-6) and the rat NEC model were used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 45 publications
1
72
0
Order By: Relevance
“…IEC6 cells (ATCC, Manassas, VA) were cultured at cell passages 17-21 in DMEM with 4 mM L-glutamine adjusted to contain 1.5 g/l sodium bicarbonate and 4.5 g/l glucose and supplemented with 10% (vol/vol) FBS, 50 U/ml penicillin and 50 g/ml streptomycin at 37°C and 5% (vol/vol) CO2 (33). Media were changed at 24 h postplating and every 72 h thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…IEC6 cells (ATCC, Manassas, VA) were cultured at cell passages 17-21 in DMEM with 4 mM L-glutamine adjusted to contain 1.5 g/l sodium bicarbonate and 4.5 g/l glucose and supplemented with 10% (vol/vol) FBS, 50 U/ml penicillin and 50 g/ml streptomycin at 37°C and 5% (vol/vol) CO2 (33). Media were changed at 24 h postplating and every 72 h thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…We have observed whorls of myelin in the SC white matter of Cbl-D rats (Scalabrino, 2009) that are similar to those of CNS autophagy, and it has been shown that abnormal autophagy plays a role in the pathogenesis of Creutzfeldt-Jakob disease and experimental scrapie (Huang and Klionsky, 2007;Levine and Kroemer, 2008;Martinez-Vicente and Cuervo, 2007;Rubinsztein et al, 2005). We tested this hypothesis by administering rapamycin to ON rats and evaluating its effect on SC white matter by means of optical and electron microscopy for the following reasons: (i) rapamycin is a pharmacological inhibitor of mTOR activity and thus stimulates autophagy (Glick et al, 2010;Huang and Klionsky, 2007;Rubinsztein et al, 2007); (ii) inhibiting mTOR reduces myelination (Norrmén and Suter, 2013;Tyler et al, 2009); (iii) as Cbl deficiency greatly reduces EGF synthesis and levels in rat CNS (see above) and EGF reduces autophagy (Maynard et al, 2010), an increase in autophagy might be expected; and (iv) Cbl deficiency increases the synthesis of TNF-␣ (see above), which has been shown to induce autophagy (Laplante and Sabatini, 2012).…”
Section: New Findings On the Pathogenesis Of Central Cbl-d Neuropathymentioning
confidence: 99%
“…Uncontrolled autophagy leads to increased survival of intracellular bacteria and an uncontrolled proinflammatory response and has been implicated in the pathogenesis of Crohn's disease (48). Our laboratory has discovered the induction of autophagy in the intestinal epithelium of NEC patients and in the rat NEC model (38). Recently, our initial observation was confirmed in the rat and mouse NEC models (43,60).…”
mentioning
confidence: 90%